Relação entre atitude sobre eutanásia e crenças religiosas - Faria, Yara Silveira (1986)
This experimental- field research was planned as the first of series of works, aiming to investigate the social- psycho!ogical aspects and implications of the euthanasia theme. Its objective was to study religious beliefs lnfluences on the attitude toward euthanasia. Six religious groups were tested , with 50 subjects in each one. The instrurnent used was the 'Escala sobre Atitude ll, an 26 items attitude scale constructed by the author of this research. This scale presented highly satisfactory coefficients of validity and reliability. It focuses, besides general aspects, the legal, medicaI and moral religious points of the problem. The relation between lnstructional leveI, sex, age and attitude toward euthanasia was analysed. The results indicated a highly significant relation between religious beliefs and attitude toward euthanasia, confirming the main hypothesis of the study. The implications of these results are discussed, and the next work of the series is being planned. It will examine the definition, conception and attitude of medicaI doctors and Iawyers toward euthanasia.